Participal phrase as basic object of syntax. (Eurasian Journal of Philology Science and Education, 2015)
This article deals with participial and verbal word-combinations and in what part of speech are their principal pairs including different roles of morphological and structural verbal word combinations. Such scientists asM.Balakaev, R.Amirov, T.Sairambayev, A.Abilakov expressed their opinion about application of verbs in the principal function and their peculiarities. I’d like to pay a special attention to the changing process of principal pairsinto subordinate pairs together with the main functions of the verbs. For this particular application of different categories of verbs in the principal function of word-combination and the participial construction is one of thecomplex problems of syntaxes and another big problem is that different explanations are given to such construction. In order to call clearly the participle construction at first, it’s necessary to show in detail the main particularities of verbs. That’s why identification of verb categories in the sentence assists to make a general decision. Differ from other parts of speech verbal word combinations are widely discussed part of speech. In connection with it to identify the application of verbs in word-combinations and parts of speech as predicate and its peculiarities are necessary fact.
Keywords: verb; word-combination; parts of speech; predicate; voice; participle; construction; mood categories; principal pair; subordinate pair